High-viscosity anti-static double-sided glass fiber adhesive tape and preparation method thereof

By using epoxy resin, carbon nanotubes and bicarboxylate quaternary ammonium polysulfone in double-sided glass fiber tape, a stable three-dimensional cross-linked mesh structure is solved, and the existing tape has poor anti-static performance and bonding performance are solved. The poor and insufficient antibacterial performance achieves higher antistatic, bonding and antibacterial properties.

CN119410280AInactive Publication Date: 2025-02-11JIANGSU AOKAI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722090.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing double-sided fiberglass tape has poor anti-static performance, poor bonding performance, and insufficient antibacterial performance, which limits its wide application in electrical, construction and other fields.

Method used

Using bisphenol A epoxy resin, epoxidized carbon nanotubes, polyamide resin, bicarboxy quaternary ammonium polysulfone, light calcium carbonate and dimethyl silicone oil, a stable three-dimensional crosslinking network is formed through chemical crosslinking reaction. Its structure improves the anti-static, bonding and antibacterial properties of the tape.

Benefits of technology

It significantly improves the anti-static, adhesive and antibacterial properties of double-sided fiberglass tape, extends its service life, and expands its application range in electrical, construction and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158292280000051
    Figure BDA0005158292280000051
  • Figure BDA0005158292280000052
    Figure BDA0005158292280000052
  • Figure BDA0005158292280000061
    Figure BDA0005158292280000061
Patent Text Reader

Abstract

The invention relates to the technical field of adhesive tapes, and discloses a high-viscosity anti-static double-sided glass fiber adhesive tape and a preparation method thereof.The adhesive is obtained by polymerizing prepared dicarboxyl quaternary ammonium salt diphenol, 4, 4-dichlorodiphenyl sulfone and bisphenol A and then mixing the mixture with bisphenol A epoxy resin, epoxidized carbon nanotubes and the like; and uniformly coating the glass fiber cloth subjected to low-temperature plasma treatment to obtain the high-viscosity anti-static double-sided glass fiber adhesive tape. The carbon nanotubes can form an infinite continuous conductive network on the surface of the adhesive tape, and the quaternary ammonium salt groups can absorb moisture in air, so that leakage of electrostatic charges and enhancement of antibacterial performance are promoted; dicarboxyl contained in dicarboxyl quaternary ammonium salt polysulfone can generate chemical crosslinking reaction with epoxy resin and epoxy groups of the epoxidized carbon nanotubes to form a three-dimensional crosslinking structure of an interpenetrating network, so that the adhesive tape matrix is endowed with better impact resistance, and the effects of strengthening and toughening are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with the application date of June 27, 2024, application number 202410844162.7, and the invention name is a high-viscosity anti-static double-sided glass fiber tape and its preparation method. Technical Field

[0002] The invention relates to the technical field of adhesive tapes, in particular to a high-viscosity antistatic double-sided glass fiber adhesive tape and a preparation method thereof. Background Art

[0003] Adhesive tape is composed of a substrate and an adhesive. Double-sided tape is a roll-shaped adhesive tape made of paper, cloth, or plastic film as the substrate, and an elastomeric pressure-sensitive adhesive or a resin-type pressure-sensitive adhesive is evenly coated on the above substrate. It is composed of three parts: a substrate, an adhesive, and a release paper (film); glass fiber double-sided tape is a tape made of glass fiber cloth as the base layer. Glass fiber tape has excellent electrical insulation properties and mechanical strength, and can effectively prevent short circuits and leakage in electrical equipment. It is widely used in various fields such as electrical, construction, automobiles, and aviation; however, in actual production and application, glass fiber materials have excellent electrical insulation properties and a high surface resistivity, and are prone to static electricity accumulation and extremely prone to static electricity. Therefore, in order to prevent static electricity from damaging electronic products, it is necessary to prepare an anti-static double-sided glass fiber tape to expand its scope of use and extend its service life.

[0004] Fiberglass tape is often used for interlayer insulation and bundling of high-frequency inverters and microwave oven transformers, bundling and fixing of metal strips, and winding and fixing of quartz tubes. It is necessary to bond multiple unconnected objects together with high strength, but the overall bonding performance of existing double-sided tape is poor, and its adhesive layer cannot meet the requirements of high-strength bonding, and cannot efficiently connect multiple unconnected objects. During the bonding process, problems such as bubbles are prone to be difficult to discharge; epoxy resin adhesive has good bonding performance, but after curing, the epoxy resin has a high cross-linking density and a three-dimensional network structure. It has the problems of large internal stress, brittleness, poor impact resistance and easy mold, which greatly limits its application in some bonding fields.

[0005] Carbon nanotubes are formed by curling graphite sheets. When compounded with epoxy resin, they can improve the mechanical properties and conductive properties of the resin. However, since the surface of carbon nanotubes is chemically inert, their dispersibility in polymer matrices is poor, which limits their application range. The present invention provides a dicarboxyl quaternary ammonium salt polysulfone, which improves the toughness and antibacterial properties of epoxy resin adhesives. The carboxyl structure of the polysulfone can produce chemical crosslinking with epoxy resin epoxidized carbon nanotubes, thereby enhancing the antistatic properties of glass fiber tapes. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-viscosity antistatic double-sided glass fiber tape and a preparation method thereof, which solves the problem of poor antistatic performance of the existing double-sided glass fiber tape and further improves the bonding performance and antibacterial performance of the tape.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A high-viscosity antistatic double-sided glass fiber tape comprises a substrate and an adhesive coated on the upper and lower surfaces of the substrate.

[0009] The substrate is glass fiber cloth treated with low-temperature plasma.

[0010] The adhesive comprises 100 parts by weight of bisphenol A epoxy resin, 5-25 parts by weight of epoxidized carbon nanotubes, 3-8 parts by weight of polyamide resin, 3-15 parts by weight of dicarboxyl quaternary ammonium salt polysulfone, 5-10 parts by weight of light calcium carbonate and 2-4 parts by weight of dimethyl silicone oil.

[0011] The preparation method of dicarboxyl quaternary ammonium salt polysulfone is as follows: under a nitrogen atmosphere, 4,4-dichlorodiphenyl sulfone, bisphenol A, dicarboxyl quaternary ammonium salt diphenol and N-methylpyrrolidone are added to a reaction flask equipped with a reflux condenser, a temperature agent and a water separator, and after stirring evenly, toluene and potassium carbonate are added, and the temperature is raised for reflux reaction, during which the water generated is taken out by toluene. After the reaction is completed, the reaction is cooled to room temperature, ethanol is added for precipitation, and the reaction is filtered to obtain dicarboxyl quaternary ammonium salt polysulfone.

[0012] Furthermore, the preparation method of the adhesive is: add bisphenol A epoxy resin, epoxidized carbon nanotubes, polyamide resin and dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1500-2000r / min and a temperature of 60-80°C, add dicarboxyl quaternary ammonium salt polysulfone and light calcium carbonate, stir for 1-3h, cool and extrude to obtain the adhesive.

[0013] Furthermore, the ratio of 4,4-dichlorodiphenyl sulfone, bisphenol A, diepoxy quaternary ammonium salt diphenol, and potassium carbonate is 1 mol: (0.8-0.95) mol: (0.05-0.2) mol: (1.9-2.3) mol.

[0014] Furthermore, the temperature-raising reflux reaction is first carried out at 135-150° C. for 1-3 h, then at 155-170° C. for 2-5 h, and finally at 180-200° C. for 3-6 h.

[0015] Further, the preparation method of dicarboxyl quaternary ammonium salt diphenol is:

[0016] Step (1), under a nitrogen atmosphere, add 3-(dimethylamino)propionic acid, phosphorus oxychloride and tetrahydrofuran to a reaction flask, stir evenly, add 4,5-dimethoxy-1,2-phenylenediamine and triethylamine, react at 20-35° C. for 12-24 h, filter and wash to obtain a dimethoxybenzene tertiary amine intermediate.

[0017] Step (2), under a nitrogen atmosphere, add a dimethoxybenzene tertiary amine intermediate and acetonitrile to a reaction flask, stir evenly, add 3-bromopropionic acid, stir to react, after the reaction is completed, add ethanol to precipitate, wash with deionized water, and dry to obtain a dimethoxybenzene dicarboxyl quaternary ammonium salt.

[0018] Step (3), under a nitrogen atmosphere, add dimethoxybenzene dicarboxyl quaternary ammonium salt and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 20-35° C. for 8-16 h, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain dicarboxyl quaternary ammonium salt diphenol.

[0019] Furthermore, in step (1), the ratio of 3-(dimethylamino)propionic acid, phosphorus oxychloride, 4,5-dimethoxy-1,2-phenylenediamine, and triethylamine is 1 mol:(3-5) mol:(0.5-0.65) mol:(1.2-1.5) mol.

[0020] Furthermore, in step (2), the ratio of the dimethoxybenzene tertiary amine intermediate to 3-bromopropionic acid is 1 mol:(2.05-2.3) mol.

[0021] Furthermore, in step (2), the reaction temperature is 65-80°C and the reaction time is 24-48h.

[0022] Furthermore, in step (3), the ratio of dimethoxybenzene dicarboxyl quaternary ammonium salt to boron tribromide is 1 mol:(2.5-3.5) mol.

[0023] Furthermore, the preparation method of the high-viscosity antistatic double-sided glass fiber tape is as follows: a glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept horizontal, and the thickness of the adhesive layer is 0.15-0.25 mm, and then placed in an oven, dried and cured at 120-140°C for 2-5 hours, and then rolled up after attaching a release film to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0024] By adopting the above technical solution, the beneficial effects of the present invention are:

[0025] The invention uses 3-(dimethylamino) propionic acid, phosphorus oxychloride, 4,5-dimethoxy-1,2-phenylenediamine and the like as raw materials, obtains dicarboxyl quaternary ammonium diphenol through condensation, demethoxylation and the like reactions, polymerizes the dicarboxyl quaternary ammonium diphenol with 4,4-dichlorodiphenyl sulfone and bisphenol A to obtain dicarboxyl quaternary ammonium polysulfone, and then mixes the dicarboxyl quaternary ammonium polysulfone with bisphenol A epoxy resin, epoxidized carbon nanotubes and the like to obtain an adhesive, and finally evenly coats the adhesive on a glass fiber cloth treated with low-temperature plasma to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0026] Epoxidized carbon nanotubes, epoxy resin and dicarboxy quaternary ammonium polysulfone form a stable three-dimensional cross-linked network structure. The carbon nanotubes can form an infinitely continuous conductive network on the surface of the tape, and then connect into a conductive path to achieve an antistatic effect. The quaternary ammonium salt groups in the dicarboxy quaternary ammonium polysulfone can absorb moisture in the air, increase the humidity of the material, and form a conductive layer on the surface of the material to reduce its surface resistivity, so that the static charge that has been generated can leak quickly, thereby inhibiting and reducing the generation of static charge. At the same time, it can also construct a conductive path so that charged particles can come into contact, further promoting the leakage of static charge and improving its antistatic performance.

[0027] The diphenyl sulfone group in the polysulfone is in a firm spatial position, which can reduce the intermolecular forces, and the ether bond can increase the flexibility of the molecular chain. The dicarboxyl group contained in the dicarboxyl quaternary ammonium salt polysulfone can produce a chemical cross-linking reaction with the epoxy resin and the epoxy group of the epoxidized carbon nanotubes to form an interpenetrating network three-dimensional cross-linked structure. At the same time, the epoxidized carbon nanotubes have good compatibility with the epoxy resin, which enhances the interfacial bonding force between the three, so that the synthesized polysulfone molecular chain is stably present in the epoxy resin. When the tape is subjected to external force, it can absorb part of the energy to disperse the stress, giving the tape matrix better impact resistance, playing a role in strengthening and toughening, and at the same time improving the bonding performance of the adhesive; the diquaternary ammonium salt structure contained in the dicarboxyl quaternary ammonium salt polysulfone has better antibacterial effect than small molecule antibacterial agents, and is not easy to produce thermal decomposition at high temperatures, thereby improving the antibacterial properties of the glass fiber tape. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The preparation method of epoxidized carbon nanotubes refers to the method of the literature "Effect of Epoxidized Modified Carbon Nanotubes on the Performance of Ortho-cresol Formaldehyde Epoxy Resin": The pH value of 120mL of anhydrous ethanol is adjusted to 4.5-5.5 with dilute hydrochloric acid, and then 5.1g of KH560 is added to prepare a mixed solution with a mass fraction of 2%, and stirred evenly, and then 0.3g of carboxylated carbon nanotubes are added, ultrasonically dispersed for 1h, and then the reactants are placed in a 60°C water bath, mechanically stirred for 6h, and then filtered, unreacted KH560 is washed with acetone, and vacuum dried at 80°C to obtain epoxidized carbon nanotubes.

[0030] Preparation of dicarboxylic quaternary ammonium salt polysulfone:

[0031] Under nitrogen atmosphere, add 1 mmol of 3-(dimethylamino)propionic acid, 3-5 mmol of phosphorus oxychloride and 5-10 mL of tetrahydrofuran to the reaction flask, stir evenly, add 0.5-0.65 mmol of 4,5-dimethoxy-1,2-phenylenediamine and 1.2-1.5 mmol of triethylamine, react at 20-35°C for 12-24 hours, filter and wash to obtain dimethoxybenzene tertiary amine intermediate. The preparation reaction formula is as follows:

[0032]

[0033] Under nitrogen atmosphere, add 1mmol of dimethoxybenzene tertiary amine intermediate and 15-25mL of acetonitrile to the reaction flask, stir evenly, add 2.05-2.3mmol of 3-bromopropionic acid, react at 65-80℃ for 24-48h, add ethanol to precipitate, wash with deionized water, and dry to obtain dimethoxybenzene dicarboxyl quaternary ammonium salt. The preparation reaction formula is as follows:

[0034]

[0035] Under nitrogen atmosphere, add 1mmol of dimethoxybenzene dicarboxyl quaternary ammonium salt and 20-30mL of dichloromethane to the reaction flask, stir evenly, add 2.5-3.5mmol of boron tribromide, react at 20-35°C for 8-16h, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain dicarboxyl quaternary ammonium salt diphenol. The preparation reaction formula is as follows:

[0036]

[0037] Under nitrogen atmosphere, add 10mmol of 4,4-dichlorodiphenyl sulfone, 8-9.5mmol bisphenol A, 0.5-2mmol dicarboxyl quaternary ammonium salt diphenol and 50-80mL of N-methylpyrrolidone to a reaction flask equipped with a reflux condenser, a temperature agent and a water separator. After stirring evenly, add 30-45mL of toluene and 19-23mmol of potassium carbonate, first react at 135-150℃ for 1-3h, then react at 155-170℃ for 2-5h, and finally react at 180-200℃ for 3-6h. The water generated during the reaction is taken out by toluene. After the reaction is completed, cool to room temperature, add ethanol for precipitation, and filter to obtain dicarboxyl quaternary ammonium salt polysulfone. The preparation reaction principle is as follows:

[0038]

[0039] Example 1

[0040] (1) Under a nitrogen atmosphere, 35 mmol of 3-(dimethylamino)propionic acid, 140 mmol of phosphorus oxychloride and 280 mL of tetrahydrofuran were added to a reaction flask. After stirring evenly, 18.2 mmol of 4,5-dimethoxy-1,2-phenylenediamine and 49 mmol of triethylamine were added. The mixture was reacted at 25° C. for 16 h, filtered and washed to obtain a dimethoxybenzene tertiary amine intermediate.

[0041] (2) Under nitrogen atmosphere, 30 mmol of dimethoxybenzene tertiary amine intermediate and 600 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 65 mmol of 3-bromopropionic acid was added. The mixture was reacted at 70° C. for 32 h, ethanol was added for precipitation, and the mixture was washed with deionized water and dried to obtain dimethoxybenzene dicarboxyl quaternary ammonium salt.

[0042] (3) Under a nitrogen atmosphere, 25 mmol of dimethoxybenzene dicarboxyl quaternary ammonium salt and 625 mL of dichloromethane were added to a reaction flask, and after stirring, 75 mmol of boron tribromide was added. The mixture was reacted at 30° C. for 12 h, and ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain dicarboxyl quaternary ammonium salt diphenol.

[0043] (4) Under a nitrogen atmosphere, 10 mmol of 4,4-dichlorodiphenyl sulfone, 9 mmol of bisphenol A, 1 mmol of dicarboxy quaternary ammonium salt diphenol and 70 mL of N-methylpyrrolidone were added to a reaction flask equipped with a reflux condenser, a temperature agent and a water separator. After stirring evenly, 40 mL of toluene and 22 mmol of potassium carbonate were added. The mixture was first reacted at 140° C. for 2 h, then at 160° C. for 5 h, and finally at 195° C. for 5 h. During this period, the water generated was taken out by toluene. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added for precipitation, and filtered to obtain dicarboxy quaternary ammonium salt polysulfone.

[0044] (5) Add 100 g of bisphenol A epoxy resin, 5 g of epoxidized carbon nanotubes, 6 g of polyamide resin and 3 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1800 r / min and a temperature of 75° C., add 3 g of dicarboxyl quaternary ammonium salt polysulfone and 8 g of light calcium carbonate, stir for 2 h, cool and extrude to obtain the product.

[0045] (6) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven and dried and cured at 130° C. for 4 h. After attaching a release film, it is rolled up to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0046] Example 2

[0047] (1) Add 100 g of bisphenol A epoxy resin, 10 g of epoxidized carbon nanotubes, 3 g of polyamide resin and 2 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 2000 r / min and a temperature of 80° C., add 6 g of dicarboxyl quaternary ammonium salt polysulfone (obtained according to the preparation method of Example 1) and 5 g of light calcium carbonate, stir for 3 h, cool and extrude to obtain the product.

[0048] (2) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.15 mm, and then placed in an oven and dried and cured at 140° C. for 2 h. After attaching a release film, it is rolled up to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0049] Example 3

[0050] (1) Add 100 g of bisphenol A epoxy resin, 15 g of epoxidized carbon nanotubes, 8 g of polyamide resin and 4 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1500 r / min and a temperature of 60° C., add 9 g of dicarboxyl quaternary ammonium salt polysulfone (obtained according to the preparation method of Example 1) and 10 g of light calcium carbonate, stir for 3 h, cool and extrude to obtain the product.

[0051] (2) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.25 mm, and then placed in an oven and dried and cured at 120° C. for 5 h. After attaching a release film, it is rolled up to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0052] Example 4

[0053] (1) Add 100 g of bisphenol A epoxy resin, 20 g of epoxidized carbon nanotubes, 5 g of polyamide resin and 3 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1600 r / min and a temperature of 65° C., add 12 g of dicarboxyl quaternary ammonium salt polysulfone (obtained according to the preparation method of Example 1) and 8 g of light calcium carbonate, stir for 3 h, cool and extrude to obtain the product.

[0054] (2) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven and dried and cured at 135° C. for 4 h. After attaching a release film, it is rolled up to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0055] Example 5

[0056] (1) Add 100 g of bisphenol A epoxy resin, 25 g of epoxidized carbon nanotubes, 4 g of polyamide resin and 4 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1800 r / min and a temperature of 70° C., add 15 g of dicarboxyl quaternary ammonium salt polysulfone (obtained according to the preparation method of Example 1) and 8 g of light calcium carbonate, stir for 2 h, cool and extrude to obtain the product.

[0057] (2) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.25 mm, and then placed in an oven and dried and cured at 140° C. for 5 h. After attaching a release film, it is rolled up to obtain a high-viscosity antistatic double-sided glass fiber tape.

[0058] Comparative Example 1

[0059] (1) Under nitrogen atmosphere, 25 mmol of the structural formula 4,5-dimethoxy-phthalic acid and 625 mL of dichloromethane were stirred evenly, and then 75 mmol of boron tribromide was added. The mixture was reacted at 30°C for 12 h, and ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain dicarboxylic diphenol.

[0060] (2) In a nitrogen atmosphere, 10 mmol of 4,4-dichlorodiphenyl sulfone, 9 mmol of bisphenol A, and 1 mmol of the structural formula were added to a reaction flask equipped with a reflux condenser, a temperature agent, and a water separator. 70 mL of dicarboxylic diphenol and 70 mL of N-methylpyrrolidone are stirred evenly, and then 40 mL of toluene and 22 mmol of potassium carbonate are added. The mixture is reacted at 140 ° C for 2 h, then at 160 ° C for 5 h, and finally at 195 ° C for 5 h. The water generated during the reaction is taken out by toluene. After the reaction is completed, it is cooled to room temperature, ethanol is added for precipitation, and filtered to obtain dicarboxylic polysulfone.

[0061] (3) Add 100 g of bisphenol A epoxy resin, 5 g of epoxidized carbon nanotubes, 6 g of polyamide resin and 3 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1800 r / min and a temperature of 75° C., add 3 g of dicarboxyl polysulfone and 8 g of light calcium carbonate, stir for 2 h, cool and extrude to obtain the product.

[0062] (4) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven and dried and cured at 130° C. for 4 h. After attaching a release film, it is rolled up to obtain a double-sided glass fiber tape.

[0063] Comparative Example 2

[0064] (1) Under nitrogen atmosphere, 10 mmol of 4,4-dichlorodiphenyl sulfone, 10 mmol of bisphenol A and 70 mL of N-methylpyrrolidone were added to a reaction flask equipped with a reflux condenser, a temperature agent and a water separator. After stirring, 40 mL of toluene and 22 mmol of potassium carbonate were added. The mixture was first reacted at 140° C. for 2 h, then at 160° C. for 5 h, and finally at 195° C. for 5 h. During the reaction, the water generated was removed by toluene. After the reaction was completed, the mixture was cooled to room temperature, ethanol was added for precipitation, and filtered to obtain polysulfone.

[0065] (2) Add 100 g of bisphenol A epoxy resin, 5 g of epoxidized carbon nanotubes, 6 g of polyamide resin and 3 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1800 r / min and a temperature of 75° C., add 3 g of polysulfone and 8 g of light calcium carbonate, stir for 2 h, cool and extrude to obtain the product.

[0066] (3) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven and dried and cured at 130° C. for 4 h. After attaching a release film, it is rolled up to obtain a double-sided glass fiber tape.

[0067] Comparative Example 3

[0068] (1) Add 100 g of bisphenol A epoxy resin, 5 g of epoxidized carbon nanotubes, 6 g of polyamide resin and 3 g of dimethyl silicone oil into a high-speed mixer, stir evenly at a speed of 1800 r / min and a temperature of 75° C., add 8 g of light calcium carbonate, stir for 2 h, cool and extrude to obtain the product.

[0069] (2) The glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state. The thickness of the adhesive layer is 0.2 mm, and then placed in an oven and dried and cured at 130° C. for 4 h. After attaching a release film, it is rolled up to obtain a double-sided glass fiber tape.

[0070] Antistatic performance test: The prepared double-sided glass fiber tape was made into a test specimen of 1 cm×3 cm×1 mm, conductive glue was coated on both ends of the specimen, and the electrical performance of the material specimen was tested using a resistance tester.

[0071] Table 1 Antistatic performance test

[0072] Surface resistivity(Ω) Example 1 <![CDATA[4.39×10 11 ]]> Example 2 <![CDATA[1.26×10 10 ]]> Example 3 <![CDATA[6.51×10 9 ]]> Example 4 <![CDATA[2.10×10 9 ]]> Example 5 <![CDATA[9.24×10 8 ]]> Comparative Example 1 <![CDATA[8.52×10 12 ]]> Comparative Example 2 <![CDATA[5.03×10 11 ]]> Comparative Example 3 <![CDATA[1.58×10 15 ]]>

[0073] From the test results in the above table, it can be seen that with the increase of the content of epoxidized carbon nanotubes and dicarboxyl quaternary ammonium salt polysulfone, the surface resistivity of the glass fiber tape gradually decreases, and in Example 5 it is reduced to 9.24×10 8 Ω, this is because, on the one hand, epoxidized carbon nanotubes form a stable three-dimensional cross-linked network structure with epoxy resin and dicarboxyl quaternary ammonium salt polysulfone, and carbon nanotubes can form an infinitely continuous conductive network on the surface of the tape. As the content of carbon nanotubes increases, they will be connected into a conductive path in the epoxy resin matrix, thereby achieving an antistatic effect; on the other hand, the quaternary ammonium salt group in the dicarboxyl quaternary ammonium salt polysulfone can absorb moisture in the air, increase the humidity of the material, and form a conductive layer on the surface of the material to reduce its surface resistivity, so that the static charge that has been generated can leak quickly, thereby inhibiting and reducing the generation of static charge; at the same time, it can also construct a conductive path so that charged particles can come into contact, further promoting the leakage of static charge and improving its antistatic performance.

[0074] Comparative Example 1 does not contain quaternary ammonium salt groups, and its antistatic performance is inferior to that of the embodiment; Comparative Example 2 contains both carbon nanotubes and quaternary ammonium salt groups, and has good antistatic performance; Comparative Example 3 does not contain carbon nanotubes and quaternary ammonium salt groups, and has no antistatic performance.

[0075] Tensile strength test: refer to GB / T 2568-1995 standard, use universal electronic tensile testing machine for testing, the tensile rate is 10mm / min.

[0076] Impact strength test: refer to GB / T 2571-1995 standard, use pendulum impact tester for testing, impact energy is 5J, sample size is 80mm×10mm×4mm.

[0077] Table 2 Mechanical properties test

[0078] Tensile strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 50.26 21.58 Example 2 55.43 22.90 Example 3 59.91 24.41 Example 4 66.42 25.38 Example 5 68.73 25.75 Comparative Example 1 50.12 21.33 Comparative Example 2 45.84 18.07 Comparative Example 3 42.32 15.65

[0079] From the test results in the above table, it can be seen that with the increase of the content of epoxidized carbon nanotubes and dicarboxyl quaternary ammonium salt polysulfone, the mechanical properties of the tape are gradually enhanced. The tensile strength in Example 4 is 66.42 MPa and the impact strength is 25.38 kJ / m 2 This is because the diphenyl sulfone group in the polysulfone is in a firm spatial position, which can reduce the intermolecular forces, the ether bond can increase the flexibility of the molecular chain, and the dicarboxyl group contained in the dicarboxyl quaternary ammonium salt polysulfone can produce a chemical crosslinking reaction with the epoxy group of the epoxy resin and the epoxidized carbon nanotubes to form a three-dimensional crosslinked structure of an interpenetrating network. At the same time, the epoxidized carbon nanotubes have good compatibility with the epoxy resin, which enhances the interfacial bonding force between the three, so that the synthesized polysulfone molecular chain is stably present in the epoxy resin. When the adhesive tape is subjected to external force, it can absorb part of the energy to disperse the stress, giving the tape matrix better impact resistance and playing a role in strengthening and toughening; in Comparative Example 2, the polysulfone molecular chain does not contain a carboxyl structure and cannot produce chemical crosslinking with the epoxy resin and the epoxidized carbon nanotubes, resulting in poor dispersion of the matrix and poor mechanical properties of the adhesive tape.

[0080] 180° peel strength test: Refer to GB / T 2792-2014 standard and use peel strength tensile tester for testing.

[0081] Tear strength test: Tested in accordance with GB / T 36878-2018 standard.

[0082] Antibacterial performance test: add 400 μL of 1.6×10 6 After the Escherichia coli solution with 0.5 CFU / mL was fully solidified, the prepared double-sided glass fiber tape was inoculated on the culture dish, placed in a 37°C constant temperature incubator for 24 hours, and the diameter of the inhibition zone was tested.

[0083] Table 3 Tape performance test

[0084]

[0085] Obviously, the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A high-viscosity antistatic double-sided glass fiber tape, characterized in that: The double-sided glass fiber tape comprises a substrate and an adhesive coated on the upper and lower surfaces of the substrate; The substrate is a glass fiber cloth treated with low-temperature plasma; The adhesive comprises 100 parts by weight of bisphenol A epoxy resin, 5-25 parts by weight of epoxidized carbon nanotubes, 3-8 parts by weight of polyamide resin, 3-15 parts by weight of dicarboxyl quaternary ammonium salt polysulfone, 5-10 parts by weight of light calcium carbonate and 2-4 parts by weight of dimethyl silicone oil; The preparation method of the dicarboxyl quaternary ammonium salt polysulfone is as follows: in a nitrogen atmosphere, 4,4-dichlorodiphenyl sulfone, bisphenol A, dicarboxyl quaternary ammonium salt diphenol and N-methyl pyrrolidone are added to a reaction flask equipped with a reflux condenser, a temperature agent and a water separator, and after being evenly stirred, toluene and potassium carbonate are added, and the temperature is raised for reflux reaction, during which water generated is taken out by toluene. After the reaction is completed, the mixture is cooled to room temperature, ethanol is added for precipitation, and the mixture is filtered to obtain the dicarboxyl quaternary ammonium salt polysulfone; the ratio of the 4,4-dichlorodiphenyl sulfone, bisphenol A, diepoxy quaternary ammonium salt diphenol and potassium carbonate is 1 mol: (0.8-0.95) mol: (0.05-0.2) mol: (1.9-2.3) mol; the heating reflux reaction is first reacted at 135-150° C. for 1-3 h, then reacted at 155-170° C. for 2-5 h, and finally reacted at 180-200° C. for 3-6 h; The preparation method of the adhesive is as follows: bisphenol A epoxy resin, epoxidized carbon nanotubes, polyamide resin and dimethyl silicone oil are added into a high-speed mixer, stirred evenly at a speed of 1500-2000 r / min and a temperature of 60-80° C., dicarboxyl quaternary ammonium salt polysulfone and light calcium carbonate are added, stirred for 1-3 hours, cooled and extruded to obtain the adhesive; The preparation method of the dicarboxyl quaternary ammonium salt diphenol is: Step (1), under a nitrogen atmosphere, add 3-(dimethylamino)propionic acid, phosphorus oxychloride and tetrahydrofuran to a reaction flask, stir evenly, add 4,5-dimethoxy-1,2-phenylenediamine and triethylamine, react at 20-35° C. for 12-24 hours, filter and wash to obtain a dimethoxybenzene tertiary amine intermediate; Step (2), under a nitrogen atmosphere, add a dimethoxybenzene tertiary amine intermediate and acetonitrile to a reaction flask, stir evenly, add 3-bromopropionic acid, stir to react, after the reaction is completed, add ethanol to precipitate, wash with deionized water, and dry to obtain a dimethoxybenzene dicarboxyl quaternary ammonium salt; Step (3), under a nitrogen atmosphere, add dimethoxybenzene dicarboxyl quaternary ammonium salt and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 20-35° C. for 8-16 hours, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain dicarboxyl quaternary ammonium salt diphenol; The preparation method of the high-viscosity antistatic double-sided glass fiber tape is as follows: a glass fiber cloth substrate is placed on a coating machine, and the prepared adhesive is evenly applied to the upper and lower surfaces of the substrate through a coating roller through a reel, a pressure roller, and a reel and kept in a horizontal state, and the thickness of the adhesive layer is 0.15-0.25 mm, and then placed in an oven, dried and cured at 120-140°C for 2-5 hours, and then rolled up after attaching a release film to obtain a high-viscosity antistatic double-sided glass fiber tape.

2. The high-viscosity antistatic double-sided fiberglass tape according to claim 1, characterized in that: In the step (1), the ratio of 3-(dimethylamino)propionic acid, phosphorus oxychloride, 4,5-dimethoxy-1,2-phenylenediamine and triethylamine is 1 mol:(3-5) mol:(0.5-0.65) mol:(1.2-1.5) mol.

3. The high-viscosity antistatic double-sided fiberglass tape according to claim 1, characterized in that: In the step (2), the ratio of the dimethoxybenzene tertiary amine intermediate to 3-bromopropionic acid is 1 mol: (2.05-2.3) mol.

4. The high-viscosity antistatic double-sided glass fiber tape according to claim 1, characterized in that: In the step (2), the reaction temperature is 65-80° C. and the reaction time is 24-48 h.

5. The high-viscosity antistatic double-sided fiberglass tape according to claim 1, characterized in that: In the step (3), the ratio of dimethoxybenzene dicarboxyl quaternary ammonium salt to boron tribromide is 1 mol: (2.5-3.5) mol.